1974
DOI: 10.1901/jeab.1974.21-89
|View full text |Cite
|
Sign up to set email alerts
|

PREFERENCE FOR AND EFFECTS OF VARIABLE‐AS OPPOSED TO FIXED‐REINFORCER DURATION1

Abstract: Pigeons were trained on multiple schedules in which a fixed number of pecks produced either a fixed or a variable period of access to food, the average variable-duration reinforcement equalling the fixed. Pecking rates were generally higher during the variableduration component. Subsequent performance on concurrent schedules revealed an initial preference for variable-duration reinforcement for all subjects; for most subjects, this preference was sustained. For one subject, the average variable duration was gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 9 publications
3
12
0
Order By: Relevance
“…A majority of studies have found evidence that subjects are risk averse (Barkan, 1990;Battalio et al, 1985;Caraco, 1982;Caraco and Lima, 1985;Clements, 1990;Hamm and Shettleworth, 1987;Kagel et al, 1986;Logan, 1965;Menlove et al, 1979;Tuttle et al, 1990). However, several studies with nonhumans have found that subjects are risk prone or indifferent Bateson and Kacelnik, 1995;Essock and Reese, 1974;Mazur, 1985;Staddon and Innis, 1966;Young, 1981).…”
Section: Choosing Between Certain and Variable Outcomesmentioning
confidence: 99%
“…A majority of studies have found evidence that subjects are risk averse (Barkan, 1990;Battalio et al, 1985;Caraco, 1982;Caraco and Lima, 1985;Clements, 1990;Hamm and Shettleworth, 1987;Kagel et al, 1986;Logan, 1965;Menlove et al, 1979;Tuttle et al, 1990). However, several studies with nonhumans have found that subjects are risk prone or indifferent Bateson and Kacelnik, 1995;Essock and Reese, 1974;Mazur, 1985;Staddon and Innis, 1966;Young, 1981).…”
Section: Choosing Between Certain and Variable Outcomesmentioning
confidence: 99%
“…Such a modification, with a 3/1 weighting, reduces the average deviation to less than 5%. Essock and Reese (1974) gave pigeons a choice between two FR 30 schedules, one leading to 5-s access to grain and the other to a variable-duration access to grain. The subjects responded more on the key that produced fixedduration access.…”
Section: Concurrent Schedulesmentioning
confidence: 99%
“…To date, there are no studies examining choice between fixed and variable doses of a drug reinforcer. When choice is between fixed and variable food amounts, results are mixed with different studies showing greater choice of a variable food amount and others showing aversion or indifference (e.g., Bateson and Kacelnik 1995; Essock and Reese 1974; Lagorio and Hackenberg 2012; McSweeney et al 2003; see Kacelnik and Bateson 1996 for a review).…”
Section: Introductionmentioning
confidence: 99%